PENERAPAN TEKNIK MNEMONIC DENGAN BAHAN AJAR BROSUR DALAM PENINGKATAN HASIL BELAJAR IPS DI KELAS V SDN 1 POHKUMBANG TAHUN AJARAN 2013/2014 - lestariani, asih (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Implementation of Mnemonic Technique with Brochure Learning Material to Improve Social Science Learning Outcome at the Fifth Grade of SDN 1 Pohkumbang in the Academic Year of 2013/2014. The objective of this research is to improve social science learning outcome at the fifth grade of SDN 1 Pohkumbang in the academic year of 2013/2014 by the implementation of mnemonic technique with brochure learning material. This research was a collaborative classroom action research (CAR). This research was conducted in three cycles. The subjects of this research were students in class V SDN 1 Pohkumbang totaling of 34 students. The result of this research indicate that the implementation of mnemonic technique with brochure learning material can imptove social science learning outcome at the fifth grade of SDN 1 Pohkumbang in the academic year of 2013/2014. Keywords: mnemonic technique, brochure, social science learning outcome Abstrak: Penerapan Teknik Mnemonic dengan Bahan Ajar Brosur dalam Peningkatan Hasil Belajar IPS di Kelas V SDN 1 Pohkumbang Tahun Ajaran 2013/2014. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar IPS di kelas V SDN 1 Pohkumbang tahun ajaran 2013/2014 melalui penerapan teknik mnemonic dengan bahan ajar brosur. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) kolaboratif. Penelitian ini dilaksanakan selama tiga siklus. Subjek penelitian ini adalah siswa kelas V SDN 1 Pohkumbang yang berjumlah 34 siswa. Hasilnya menunjukkan bahwa penerapan teknik mnemonic dengan bahan ajar brosur dapat meningkatkan hasil belajar IPS di kelas V SDN 1 Pohkumbang tahun ajaran 2013/2014. Kata kunci: teknik mnemonic, brosur, hasil belajar IPS